Clinical and Physiologic Factors Associated With Mode of Death in Pediatric Severe TBI - Baird, Talia D.; Miller, Michael R.; Cameron, Saoirse; Fraser, Douglas D.; Tijssen, Janice A. (Frontiers in Pediatrics, 2021)
Aims & Objectives: Severe traumatic brain injury (sTBI) is the leading cause of death in children. Our aim was to determine the mode of death for children who died with sTBI in a Paediatric Critical Care Unit (PCCU) and evaluate factors associated with mortality. Methods: We performed a retrospective cohort study of all severely injured trauma patients (Injury Severity Score ≥ 12) with sTBI (Glasgow Coma Scale [GCS] ≤ 8 and Maximum Abbreviated Injury Scale ≥ 4) admitted to a Canadian PCCU (2000–2016). We analyzed mode of death, clinical factors, interventions, lab values within 24 hours of admission (early) and pre-death (48 hours prior to death), and reviewed meeting notes in patients who died in the PCCU. Results: Of 195 included patients with sTBI, 55 (28%) died in the PCCU. Of these, 31 (56%) had a physiologic death (neurologic determination of death or cardiac arrest), while 24 (44%) had withdrawal of life-sustaining therapies (WLST). Median (IQR) times to death were 35.2 (11.8, 86.4) hours in the physiologic group and 79.5 (17.6, 231.3) hours in the WLST group (p=0.08). The physiologic group had higher partial thromboplastin time (PTT) within 24 hours of admission (p=0.04) and lower albumin prior to death (p=0.04). Conclusions: Almost half of sTBI deaths in the PCCU were by WLST. There was a trend towards a longer time to death in these patients. We found few early and late (pre-death) factors associated with mode of death, namely higher PTT and lower albumin.